2019
DOI: 10.1158/1541-7786.mcr-18-0968
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of the Forkhead Box Factors FoxM1 and FoxA2 in Liver Cancer

Abstract: The forkhead box transcription factor FoxM1 is essential for hepatocellular carcinoma (HCC) development, and its overexpression coincides with poor prognosis. Here, we show that the mechanisms by which FoxM1 drives HCC progression involve overcoming the inhibitory effects of the liver differentiation gene FoxA2. First, the expression patterns of FoxM1 and FoxA2 in human HCC are opposite. We show that FoxM1 represses expression of FoxA2 in G 1 phase. Repression of FoxA2 in G 1 phase is important, as it is capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Not only that, it was also found that FOXM1 contributes to tumor angiogenesis in the study of colorectal and gastric cancer [23, 32]. In previous studies, there was a large amount of evidence that FOXM1 directly or indirectly affects the occurrence and development of HCC, which is in line with our results [2729, 3339]. In addition, in an in vivo study of HCC, the growth of tumors in mice with FOXM1 deficiency was completely stagnated, suggesting that FOXM1 has the potential to become an independent biomarker of HCC [31].…”
Section: Discussionsupporting
confidence: 91%
“…Not only that, it was also found that FOXM1 contributes to tumor angiogenesis in the study of colorectal and gastric cancer [23, 32]. In previous studies, there was a large amount of evidence that FOXM1 directly or indirectly affects the occurrence and development of HCC, which is in line with our results [2729, 3339]. In addition, in an in vivo study of HCC, the growth of tumors in mice with FOXM1 deficiency was completely stagnated, suggesting that FOXM1 has the potential to become an independent biomarker of HCC [31].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, SP1 [ 19 ], E2F3 [ 32 ] and YAP1 [ 33 ] previously reported as important regulators/interactors of HELLS and E2F7 as an important mediator of P53 target gene repression [ 34 , 35 ] were not altered at the transcript level under Nutlin-3a treatment. However, as the most strikingly downregulated TF with a link to P53/P21 [ 36 ], and high relevance in liver cancer [ 37 , 38 , 39 , 40 ] we identified FOXM1 ( Figure 5 A and Table S1 ). Consistent with previous findings in HepG2 [ 36 ] we could validate a strong downregulation of FOXM1 protein and mRNA upon Nutlin-3a treatment also in HUH6 and Sk-Hep1 cells ( Figure 5 B–E).…”
Section: Resultsmentioning
confidence: 99%
“…FOXM1 is a transcription factor that regulates cell proliferation, cell cycle progression, cell differentiation, DNA damage repair, tissue homeostasis, angiogenesis, and apoptosis [ 10 , 11 , 20 ]. Indeed, previous studies have reported that the increased expression of FOXM1 affects tumor growth and drug resistance in various solid tumors [ 21 , 22 , 23 , 24 ]. In this study, we clarified that FOXM1 was retained by dispersed chromatin at the M phase, when the bulk of DNA-binding proteins are excluded from condensed chromosomes [ 25 ], as analyzed by super-resolution microscopy image analysis.…”
Section: Discussionmentioning
confidence: 99%